2009
DOI: 10.1016/j.placenta.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental Adenosine Receptor Expression is Elevated in Preeclampsia and Hypoxia Increases Expression of the A2A Receptor

Abstract: Placental hypoxia as a result of impaired trophoblast invasion is suggested to be involved in the pathophysiology of preeclampsia. Hypoxia is a potent stimulus for the release of adenosine, and the actions of adenosine are mediated through four adenosine receptors, A 1 , A 2A , A 2B and A 3 . We investigated the presence, distribution and expression of adenosine receptor subtypes in the human placenta, the expression of the adenosine receptors in placentas from pregnancies complicated by preeclampsia, small fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 41 publications
(43 reference statements)
4
42
1
Order By: Relevance
“…In this study, we have found a reduced amount of A 2A AR protein in cells from EOPE, without changes in cells from LOPE, compared to normal pregnancies. These results are linked with our previous results [20] where a low expression of A 2A AR was reported in hPMEC from preeclampsia, but disagree with previous analysis using total placental homogenate from preeclampsia, where high expressions of all adenosine receptors have been shown [31]. Methodological differences may explain this a c b d controversy.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, we have found a reduced amount of A 2A AR protein in cells from EOPE, without changes in cells from LOPE, compared to normal pregnancies. These results are linked with our previous results [20] where a low expression of A 2A AR was reported in hPMEC from preeclampsia, but disagree with previous analysis using total placental homogenate from preeclampsia, where high expressions of all adenosine receptors have been shown [31]. Methodological differences may explain this a c b d controversy.…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, even though the expressions of A 2A AR and A 2B AR in HUVECs are well described [23,32,33], our data reinforce the importance of classifying into EOPE and LOPE when studying preeclampsia, as in this analysis; they presented important pathophysiological differences which seem to not have a relationship with gestational age. In this regard, and despite we have not studied the mechanisms linked with those differences, but considering that hypoxia upregulates A 2A AR expression in placental explants [31] and epithelial cells [34,35], it is interesting to speculate that the differences observed in the expression of A 2A AR in EOPE and LOPE might suggest different capacities to respond to hypoxia in those conditions. This hypothesis is reinforced by recent evidence [36] showing that villous explants extracted from EOPE and cultured under varying oxygen tensions exhibited reduced levels of hydroxylated hypoxia-inducible factor type 1 alpha, a phenomenon that was absent in LOPE.…”
Section: Discussionmentioning
confidence: 96%
“…Both subtypes of purinergic receptors have widespread tissue expression, including the placenta (see Tables S2 and S3). 5,24,25 …”
Section: Atp and Adenosinementioning
confidence: 99%
“…P1 and P2X 4 receptors were found to be increased in placental tissue from preeclamptic compared with normal pregnant women. 24,101 Interestingly, under hypoxic conditions in vitro, placental explants from normal pregnancies showed increased expression of the A 2A receptor. 24 This may be a compensatory mechanism to increase the vasodilatory effect of adenosine.…”
Section: Pathophysiological Role Of Increased Plasma Atp and Adenosinmentioning
confidence: 99%
“…Women with pre-eclampsia and foetuses show increased circulating concentrations of adenosine. Adenosine A 2A receptors expression is elevated in placental biopsies, villous explants and placental microvillous membranes [423]. A 2B receptors on microvascular endothelial cells have also been implicated in pre-eclampsia [108].…”
Section: Placentamentioning
confidence: 99%